UR_GERICHTE 2016_OG BI 16 6. vom 29. August 2016 - UR Obergericht (2016)
Strafprozessordnung. Art. 52 SDÜ. Art. IIIA lit. b ZV-D/EUeR. Art. 85 Abs. 2, 3 und 4 lit. a, Art. 90 Abs. 1, Art. 354 Abs. 1 StPO.